The Relationship between SBAR Method during Handover and Nurse Job Satisfaction at RSUD Lembang - Anisa Adawiah; Heri Ridwan; Iyos Sutresna (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
SBAR communication is a communication method used when nurses carry out handovers to patients. This study aims to analyze the relationship between the application of the SBAR method during handover and the level of job satisfaction of nurses in the Lembang Hospital inpatient room. This research was carried out by taking 35 respondents involving all nurses in the Lembang Regional Hospital's inpatient room. The results of this research stated that Ha was accepted with (p = 0.033), which means there is a significant relationship between SBAR communication and nurses' job satisfaction. The conclusion of this research is that the application of the SBAR method during handover has a positive relationship with nurses' job satisfaction at Lembang Regional Hospital, confirming the importance of communication training and the use of structured communication methods such as SBAR in nursing practice to increase job satisfaction and potentially improve safety and the quality of patient care.